Pengaruh Pergantian Manajemen, Finansial Distress, Opini Audit, dan Audit Delay Terhadap Auditor Switching pada Perusahaan Manufaktur - Novi Rahmitasari; Ahmad Syarief (Indonesian Accounting Literacy Journal, 2021)
This study aims to examine the effect of management change, financial distress, audit opinion, and audit delay on auditor switching. The population of this study uses 200 manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This type of research is quantitative research with secondary data, statement data for audited each manufacturing company for the 2014-2018 period. The sample used in this study consisted of 43 companies selected using purposive sampling method. The data analysis technique used panel data regression test using Eviews 9. The results of this study indicate that management change, financial distress, audit opinion, and audit delay have a simultaneous effect on auditor switching. However, partially management change and variables financial distress have an effect on auditor switching. Meanwhile, the audit opinion and variables audit delay have no effect on auditor switching.